BEHAVIOUR PROBLEMS OF ADOLESCENTS IN SECONDARY SCHOOLS OF BULAWAYO: CAUSES, MANIFESTATIONS AND EDUCATIONAL SUPPORT - CHIMHENGA, Dr. SYLOD (IJRDO- Journal of Educational Research, 2017)
Behaviour problems frustrate many teachers and create an unpleasant teaching and learningenvironment. When disruptive interactions occur between teachers and learners, these sometimeslead to a chain of actions and reactions that spiral out of control resulting in chaos in theclassroom. Behaviour problems are a problem in many secondary schools in Zimbabwe. Thisstudy investigated the causes and manifestations of behaviour problems of adolescent learnersand suggested guidelines for teachers on how to assist learners with behaviour problems in theclassroom. This is a quantitative study that used questionnaires. The questionnaire items for thisstudy were in the form of a four or five point Likert-Scale. The main findings contributing to thecauses of behaviour problems among adolescent learners are environmental factors, such as thefamily and the school and peer pressure. Behaviour problems are manifested by adolescents asdisruptive behaviour, aggressive and antisocial behaviour, telling lies and theft. The findingshighlight important guidelines, which teachers can use to assist and understand learners withbehaviour problems in the classroom. The guidelines present an endeavour to solve problembehaviour in the classroom.